Terobosan Hukum Pidana melalui Penghentian Penuntutan Perkara Tindak Pidana Umum Berdasarkan Keadilan Restoratif - I Nyoman Triarta Kurniawan; I Made Wirya Darma (VYAVAHARA DUTA, 2023)
The Attorney General's Office as a law enforcement agency is required to play a role in upholding the rule of law, protecting public interests, upholding human rights, and eradicating corruption, collusion and nepotism. Demands for the efficiency of case resolution, protection of human rights are the roots of the emergence of case settlements through restorative justice. This research will discuss the authority of prosecution by prosecutors in the criminal justice system and termination of prosecution based on restorative justice as a legal breakthrough. This legal breakthrough allows for the termination of prosecution as stipulated in the Attorney General's Regulation of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The research method used in this writing is an empirical research method which uses primary data and secondary data and with data collection techniques through interviews. Based on the interview results obtained, it can be analyzed that the role of the prosecutor in stopping prosecution based on restorative justice is as a negotiator and facilitator between the two parties, namely the suspect and the victim for a peace agreement which is used as the basis for consideration in stopping criminal cases, but even so, not all criminal cases can be resolved with Restorative Justice.